2017
DOI: 10.1590/s1677-5538.ibju.2015.0521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of various potential prognostic markers and survival data in clear cell renal cell carcinoma

Abstract: Purpose Clear cell renal cell cancers frequently harbor Von Hippel-Lindau gene mutations, leading to stabilization of the hypoxia-inducible factors (HIFs) and their target genes. In this study, we investigated the relationship between vascular endothelial growth factor (VEGF), HIF-1α, HIF-2α, p53 positivity, microvessel density, and Ki-67 rates with prognostic histopathologic factors (Fuhrman nuclear grade, stage, and sarcomatoid differentiation) and survival in clear cell renal cell carcinomas.Material and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
8
16
0
3
Order By: Relevance
“…In the multivariable model, male sex, stage ≥T3, tumor size, Fuhrman grade, and sarcomatoid differentiation were related only to the survival (p<0.05, S1 Table) similar to that reported in previous studies [4, 29, 30]. …”
Section: Discussionsupporting
confidence: 85%
“…In the multivariable model, male sex, stage ≥T3, tumor size, Fuhrman grade, and sarcomatoid differentiation were related only to the survival (p<0.05, S1 Table) similar to that reported in previous studies [4, 29, 30]. …”
Section: Discussionsupporting
confidence: 85%
“…In our study, most of the RCC cases were VEGF as grade-1 (42.0%) while 38% cases were VEGF grade-2 and 20% were VEGF grade-0 or with no staining which corroborate with the findings of Ebru T et al 19 who got only 4 cases which did not show staining while 27 cases (37.5%) showed strong VEGF staining.…”
Section: Figure 1 Hande Photomicrographs Of Different Subtypes Of Rccssupporting
confidence: 91%
“…This was similar to the studies done by Yildiz E et al, 16 Bürgesser M et al 18 and Osman WM et al 21 Expression of VEGF grades was seen to increase with the increase in stage of the tumours. This observation was found to be concordant with Ebru T et al, 19 Bürgesser M et al 18 and Osman WM et al 21 No significant difference was found in our study between different RCC types concerning cytoplasmic VEGF expression which is concordant with findings of Yildiz E et al 16 and Matušan-Ilijaš K et al 22 Furthermore, we noted that VEGF grade showed significant association with presence of necrosis and lymphovascular invasion which is similar to studies by Fujita N et al 23 and Veselaj F et al 24 In our study, we found the mean Ki-67 labelling index (mean ± s.d.) of the patients was 14.32 ± 3.88 with a range 5 -22 and the median was 15.0.…”
Section: Figure 1 Hande Photomicrographs Of Different Subtypes Of Rccssupporting
confidence: 91%
“…There was also selection bias in the selection and exclusion of patients, because we only selected the patients with complete information. In addition, many factors were not included, such as the statuses of VEGF, HIF-1α, HIF-2α, p53, and Ki-67 40,41 , which have been shown to in uence the prognosis of ccRCC. Because the included subjects had a higher survival rate and fewer subjects died during the follow-up period, the Validation curve only showed the portion with high survival rate.…”
Section: Limitationsmentioning
confidence: 99%